Computational analysis of retinal image quality with different contact lens designs in keratoconus. Issue 2 (April 2023) - Devi, Preetirupa; Kumar, Preetam; Bharadwaj, Shrikant R.
Abstract: Purpose: To determine 1) the relative differences in optical quality of keratoconic eyes fitted with four routinely used CL designs and 2) the Zernike coefficients in the residual wavefront aberration map that may be responsible for differences in the optical quality of keratoconic eyes fitted with these CLs. Methods: Wavefront aberrations over a 3-mm pupil diameter were measured without and with Kerasoft IC®, Rose K2®, conventional spherical Rigid Gas Permeable (RGP), and Scleral CLs in 15 mild to moderate keratoconic eyes (20 – 28 years) and under unaided viewing in 10 age-similar non-contact lens wearing controls. The resultant through-focus curves constructed for the logarithm of Neural Sharpness (logNS) Image Quality (IQ) metric were quantified in terms of peak value, best focus, and depth of focus. Sensitivity analyses determined the impact of the residual Zernike coefficients of keratoconic eyes fitted with CLs on the IQ of controls at emmetropic refraction. Results: The peak IQ and depth of focus were similar with Rose K2®, conventional RGP, and Scleral CLs (p > 0.05, for all) but significantly better than Kerasoft IC® CLs (p < 0.01 for all). Best focus was similar across all four CLs (p > 0.2 for all). However, the IQ parameters of all the lenses remained significantly poorer than the controls (p < 0.01, for all). The IQ of the controls dropped to keratoconic levels with induced residual lower-order Zernike terms and 3rd-order coma across all lenses in the sensitivity analysis (p < 0.001). Conclusions: IQ of keratoconic eyes remain suboptimal with routinely dispensed CL designs, largely due to residual lower-order aberrations and coma, all relative to the controls. The performance drop appears greater for the Kerasoft IC® CL relative to the other CL designs. These results may provide the optical basis for psychophysical spatial visual performance reported earlier across these four CL designs for keratoconus.